2003
DOI: 10.1021/jp034785h
|View full text |Cite
|
Sign up to set email alerts
|

Energy Releasing and Conformational Dynamics of Stilbene Dendrimers upon Photoisomerization

Abstract: The energy-releasing process and the conformational dynamics of stilbene dendrimers (tetramethoxystilbene (generation (G) 0, G1, G2, and G4) upon photoexcitation are studied by the time-resolved transient grating method. For all dendrimers, the excited triplet (T1) state formation was observed. From the time-resolved studies on energy and the molecular volumes changes, it is found that the conformational change completes with the decay of the T1 state for G0−G2. However, the dynamics is slightly slower for G4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…In addition, the changes in the TADF decay dynamics were negligible before, during, and after, e.g., 3 days of irradiation (see Supplementary Figs. 17,20). The results are indicative of the retardation of triple-triplet energy transfer and hence a lack of NBD → QC isomerization.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the changes in the TADF decay dynamics were negligible before, during, and after, e.g., 3 days of irradiation (see Supplementary Figs. 17,20). The results are indicative of the retardation of triple-triplet energy transfer and hence a lack of NBD → QC isomerization.…”
Section: Resultsmentioning
confidence: 92%
“…Energy storage can also be accomplished through photoisomerization 8 . A considerable number of molecular solar thermal (MOST) systems incorporating organic compounds, including anthracene 9,10 , azobenzene [11][12][13] , dihydroazulene 14,15 , norbornadiene-quadricyclane [16][17][18] , stilbene 19,20 , and ruthenium fulvalene derivatives 21,22 , which can undergo light-induced isomerization to metastable isomers for storage of solar energy, have been proposed.…”
mentioning
confidence: 99%
“…Clear evidence for the large conformational change upon isomerization of stilbene (tetramethoxystilbene) dendrimers of generation G0, G1, G2, and G4 was presented [105]. From the time-resolved studies on energy and molecular volumes changes, it was found that the conformational change upon the trans-to cis-isomerization completed with the decay of the T 1 state for G0-G2.…”
Section: Stilbene Photoisomerization In Dendrimersmentioning
confidence: 99%
“…In this area, the photoisomerization of dendrimers with photoresponsive cores-such as stilbene, [13][14][15][16][17][18][19][20][21] azobenzene, [22][23][24][25][26][27][28][29][30][31][32][33] diarylethene, [34][35][36][37][38] intramolecularly hydrogen-bonded chromophores, [39][40][41] and photolabile chromophores 42-44 -has been extensively investigated. We recently reported that stilbene dendrimers with benzyl ether-type dendrons exhibited a volume-conserving isomerization mechanism and a macromolecular effect (or generation effect) on energy transfer efficiency from the peripheral dendrons to the core stilbene in organic solvents [45][46][47] and aqueous solution. [48][49][50] In these cases, the core stilbene unit played an important role as a photo-trigger for large conformational changes (photoisomerization), and as a fluorescent probe for detecting the environment inside the dendrimer.…”
Section: Introductionmentioning
confidence: 99%